Shikonin Induces Glioma Necroptosis, Stemness Decline, and Impedes (Immuno)Proteasome Activity - Xianyun Qin; Lu Zhang; Jilan Liu; Yan Lu; Fuyao Zhou; Feng Jin (Stem Cells International)
Gliomas, the most prevalent primary intracranial tumors, exhibit notable features such as heightened malignancy, rapid recurrence, and elevated mortality rates. Presently, standard therapeutic approaches yield limited curative outcomes. Shikonin, an extract derived from traditional Chinese medicine, demonstrates notable bioactivity against various tumors, including gliomas. This study elucidates Shikonin’s capacity to effectively induce necroptosis in glioma cells, concurrently mitigating glioma stemness, as evidenced by diminished levels of stem cell markers, namely SOX2, CD44, CHI3L1, and CD24. Our findings indicate that Shikonin-induced programed necrosis leads to a downregulation of proteasome activity and a decrease in the expression of immune proteasome subunits PSMB8/9/10 and PSME1/2/3, contributing to the attenuation of stemness in gliomas. This study comprehensively investigates the interplay between (immuno)proteasome dynamics, Shikonin-mediated necroptosis, and the consequential reduction in glioma stemness, both in vitro and in vivo. The discussion extends to the potential of Shikonin as a promising therapeutic agent in the management of gliomas, offering a novel avenue for drug development in this challenging clinical context.